Do different survey methods affect physicians’ stated work preferences? Findings from a discrete choice experiment in Eastern China - Lizhu Wang; Lizhu Wang; Dan Hu; Dan Hu; Jing Zhu (Frontiers in Sociology)
ObjectivesThis study aimed to examine the impact of online and offline survey methods on the participation of physicians in discrete choice experiment (DCE) surveys in Eastern China and explore their attitudes towards primary healthcare work.MethodsThe study involved active doctors practicing at secondary or county-level general hospitals in Eastern China, who completed a DCE questionnaire either online or offline. A mixed logit model was used to analyze the data, considering the relative importance of various job attributes.ResultsThis study found that online surveys save costs and offline surveys help increase the response rate for questionnaires. The validity rate for the completed questionnaires was high (>90%) across both research methods. A mixed logit model simulation analysis revealed that compensation packages were the dominant influence on doctors’ choices. The online survey showed that doctors were more likely to choose to work in village health centers if their salary was flat (β = 1.330), while the offline survey showed that doctors were also more likely to choose village health centers when their salary was increased by 10% (β = 1.095). Work organization and public recognition also had a significant effect on doctors’ primary job choices (p < 0.05).ConclusionThe study concluded that remuneration, work organization, and public recognition are key factors affecting physicians’ willingness to work in primary healthcare settings. For respondents with higher education and cognitive abilities, online surveys are recommended for DCE research.